The International Monetary System : Where Are We and Where Do We Need to Go? - Mohan, Rakesh (IMF Working Papers; Working Paper ;, 2013)
The North Atlantic financial crisis of 2008-2009 has spurred renewed interest in reforming the international monetary system, which has been malfunctioning in many aspects. Large and volatile capital flows have promoted greater volatility in financial markets, leading to recurrent financial crises. The renewed focus on the broader role of the central banks, away from narrow price stability monetary policy frameworks, is necessary to ensure domestic macroeconomic and financial stability. Since international monetary cooperation might be difficult, though desirable, central banks in major advanced economies, going forward, need to internalize the implications of their monetary policies for the rest of the global economy to reduce the incidence of financial crises.